Tracing sediment sources in an agriculture and livestock catchment of Argentina through the use of geochemical fingerprints - Torres Astorga, Romina Vanesa (2019)
A mixing modelling approach (CSSIAR v2.00), using Energy Dispersive X Ray Fluorescence (EDXRF) and Total Organic Carbon (TOC) data as fingerprints for sediment sources and sinks, was applied for identifying critical hot spots of erosion in a typical Argentinian agro-ecosystem. The selected study site is the Estancia Grande catchment, covering 1235 hectares, which is located 23 km north east of San Luis (in the centre of Argentina). The studied catchment, which is characterized by highly erodible Haplic Kastanozem soils, is currently being used for agriculture (crop rotation), and livestock (free grazing and feedlots), and some fields are used for growing nut trees (walnuts and almonds) (Figure 1). Further fallow land is found in between the agriculture land and in the upper part of the catchment.